2020
DOI: 10.12659/ajcr.917376
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Metastasis Masquerading as Primary Colon and Gastric Cancer: A Case Report

Abstract: Unusual clinical course Background: Breast cancer is the most common malignancy in women worldwide. Despite treatment, recurrence and metastasis are common. Lobular breast cancer most commonly metastasizes to the lungs, liver, lymph nodes, and sites in the brain. Metastasis to the gastrointestinal tract is rare, with few cases reported to date. Case Report: This report describes a patient with late colon and gastric metastases from lobular breast cancer mimicking primary colon and gastric cancers. Conclusions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Moreover, immunohistochemistry for cytokeratin 20 (CK-20) and caudal-type homeobox 2 (CDX2) can accurately identify colon adenocarcinoma origin [3]. Cytokeratin 7 (CK-7) is positive for most breast cancers, but negative for colon cancer [11]. In this case, the patient's immunohistochemistry of the breast showed that CK-20 positive expression, CDX-2 weakly positive expression and CK-7 negative expression, which con rmed the intestinal tract origin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immunohistochemistry for cytokeratin 20 (CK-20) and caudal-type homeobox 2 (CDX2) can accurately identify colon adenocarcinoma origin [3]. Cytokeratin 7 (CK-7) is positive for most breast cancers, but negative for colon cancer [11]. In this case, the patient's immunohistochemistry of the breast showed that CK-20 positive expression, CDX-2 weakly positive expression and CK-7 negative expression, which con rmed the intestinal tract origin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Noor and colleagues reported a case of a 68-year-old female with ILC BC, presenting 30 years after the initial diagnosis of BC, with symptoms of obstruction. CT confirmed circumferential narrowing and thickening in the distal sigmoid colon [ 8 ], and due to her history of BC, a decision was made to investigate with colonoscopy first. Colonoscopy revealed diffuse proliferation of neoplastic cells, with histochemistry confirmation of metastatic BC [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT confirmed circumferential narrowing and thickening in the distal sigmoid colon [ 8 ], and due to her history of BC, a decision was made to investigate with colonoscopy first. Colonoscopy revealed diffuse proliferation of neoplastic cells, with histochemistry confirmation of metastatic BC [ 8 ]. Further investigation with endoscopy also revealed gastric metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the literature, the GI tract was rarely a preferred metastatic site for breast cancer in particular [ 10 ]. Thus Apodaca-Rueda M et al had reported a case of metastasis to the pancreatic level [ 11 ], Nour A et al, described a metastasis to both the colonic and gastric level initially taken as primary [ 12 ]. Other authors report digestive metastases of a breast primary discovered in a context of complication or emergencies like Théraux J et al who had described a colonic occlusion on a colonic tumor of breast origin [ 13 ] and Nehmeh WA et al had reported a secondary localization following a gastric perforation [ 14 ], while hematemesis revealed the diagnosis in our case.…”
Section: Discussionmentioning
confidence: 99%